1993
DOI: 10.1016/0014-5793(93)80453-2
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor protects cerebellar neurons in primary culture from NMDA and non‐NMDA receptor mediated neurotoxicity

Abstract: We have investigated the ability of bFGF to protect cerebellar neurons from neurotoxicity by excitatory amino acids. We have found that preincubation with l-2.5 nM bFGF for l-6 days significantly protected neurons from excitotoxic damage via NMDA receptors as well as ionotropic non-NMDA receptors. bFGF neuroprotection appeared not to be dependent upon neuronal differentiation and was not mimicked by other neurotrophins including BDNF. NT-3 and NGF. A greater rise in extracellular calcium-dependent cGMP formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 38 publications
(9 reference statements)
4
32
0
Order By: Relevance
“…If microglia are contributing to the enhancement of excitotoxicity, it is unlikely to be via activation of iNOS, because cultures lacking nNOS fail to exhibit neurotrophin-mediated enhancement of excitotoxic injury. When neurons are grown on a Poly-O matrix, BDNF pretreatment is neuroprotective, consistent with numerous previous reports of the protective role of neurotrophins (Mattson et al, 1989Fernandez-Sanchez and Novelli, 1993;Nozaki et al, 1993;Prehn et al, 1993;Burke et al, 1994;Lindholm, 1994;Lindvall et al, 1994;Nakao et al, 1995;Anderson et al, 1996). Thus, the phenotype of neuronal cultures is influenced markedly by the culture paradigm.…”
Section: Discussionsupporting
confidence: 72%
“…If microglia are contributing to the enhancement of excitotoxicity, it is unlikely to be via activation of iNOS, because cultures lacking nNOS fail to exhibit neurotrophin-mediated enhancement of excitotoxic injury. When neurons are grown on a Poly-O matrix, BDNF pretreatment is neuroprotective, consistent with numerous previous reports of the protective role of neurotrophins (Mattson et al, 1989Fernandez-Sanchez and Novelli, 1993;Nozaki et al, 1993;Prehn et al, 1993;Burke et al, 1994;Lindholm, 1994;Lindvall et al, 1994;Nakao et al, 1995;Anderson et al, 1996). Thus, the phenotype of neuronal cultures is influenced markedly by the culture paradigm.…”
Section: Discussionsupporting
confidence: 72%
“…This potential increase in vulnerability to apoptosis may be amplified by the dysregulation in growth factors we have observed in the same brains, particularly the FGF system (14). Indeed, it is conceivable that the dysregulation in growth factors plays a causative role in increased apoptosis and in the altered expression of glial-based glutamate transporters (38). In turn, because metabotropic glutamate receptors are coupled to G protein receptors and act on various second messenger systems, the effects could be even more far reaching through modulation of numerous downstream signaling mechanisms.…”
Section: Discussionmentioning
confidence: 76%
“…These findings contrast with those of previous reports, in which activation of the glutamate pathway led to upregulation of BDNF transcription in cerebellar granule neurons (Bessho, Nakanishi, & Nawa, 1993;Favaron et al, 1993;Lindholm, Dechant, Heisenberg, & Thoenen, 1993;Wu et al, 2004), which may be explained by the specificity of the transcription product targeted in this study. The increased levels of BDNF expression in these cases protected the cells from the toxic effects of excess glutamate; however, other studies have reported that administration of exogenous BDNF can prove either protective or detrimental to cells undergoing excitotoxic insults (Almeida et al, 2005;Brandoli et al, 1998;Cheng & Mattson, 1994;Fernández-Sánchez & Novelli, 1993;Koh, Gwag, Lobner, & Choi, 1995;Kume et al, 1997;Mattson et al, 1995;Prehn, 1996;Samdani et al, 1997;Skaper, Floreani, Negro, Facci, & Giusti, 1998). It will be important to ascertain whether the alteration in BDNF levels in these cells is a protective response, or part of the cascade of events leading to cell death.…”
Section: Discussionmentioning
confidence: 95%